The impact of early factors on persistent negative symptoms in youth at clinical high risk for psychosis - Devoe, Daniel J.; Lui, Lu; Cannon, Tyrone D.; Cadenhead, Kristin Suzanne; Cornblatt, Barbara A.; Keshavan, Matcheri; McGlashan, Tom H.; Perkins, Diana. O.; Seidman, Larry J.; Stone, William S.; Tsuang, Ming T.; Woods, Scott W.; et al. (Frontiers in Psychiatry, 2023)
Introduction Persistent negative symptoms (PNS) are described as continuing moderate negative symptoms. More severe negative symptoms have been associated with poor premorbid functioning in both chronic schizophrenia and first episode psychosis patients. Furthermore, youth at clinical high risk (CHR) for developing psychosis may also present with negative symptoms and poor premorbid functioning. The aim of this current study was to: (1) define the relationship between PNS and premorbid functioning, life events, trauma and bullying, previous cannabis use, and resource utilization, and (2) to examine what explanatory variables best predicted PNS. Method CHR participants (N = 709) were recruited from the North American Prodrome Longitudinal Study (NAPLS 2). Participants were divided into two groups: those with PNS (n = 67) versus those without PNS (n = 673). A K-means cluster analysis was conducted to distinguish patterns of premorbid functioning across the different developmental stages. The relationships between premorbid adjustment and other variables were examined using independent samples t-tests or chi square for categorical variables. Results There was significantly more males in the PNS group. Participants with PNS had significantly lower levels of premorbid adjustment in childhood, early adolescence, and late adolescence, compared to CHR participants without PNS. There were no differences between the groups in terms of trauma, bullying, and resource utilization. The non-PNS group had more cannabis use and more desirable and non-desirable life events. Conclusion In terms of better understanding relationships between early factors and PNS, a prominent factor associated with PNS was premorbid functioning, in particular poor premorbid functioning in later adolescence.